Mental skills training in elite sports environments: Current status of integration - Walsh, A.; du Plooy, K. (The Journal of Sport and Exercise Science, 2023)
The role of mental skills training (MST) in elite sports is continually growing in prominence as several studies have emphasized its value to athletes and coaches for several years. Fewer studies have investigated how MST might successfully be integrated into elite sports franchises, clubs, and teams. This study examined the current status of MST integration in these environments. It also explored the obstacles to successful integration and how these might be overcome. A qualitative approach and phenomenological design were employed to collect data via emailed open-ended questions and follow-up semi-structured in-depth interviews and the data was analysed through thematic analysis (TA). Thirty-five leaders working in elite sports participated. Findings revealed that while all participants (n = 35) endorsed the importance of MST in elite sports, 11% (n = 4) had incorporated it effectively into their environments. Unsuitable practitioners, a lack of leadership support, and insufficient time for successful application were highlighted as significant obstacles hindering successful integration. Recommendations to overcome these obstacles included the prioritisation of MST by leaders of elite sports environments, formulating bespoke MST strategies for their teams, clubs, or franchises, recruiting suitably qualified MST providers, and providing them with sufficient time and resources to effectively implement these strategies.